Sexual Politics and Marital Rape in Indonesia - Fauzy, Ahmad Tsalis Fakhrul; Maharani, Septiana Dwiputri (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
Marital rape has become a hot topic of conversation in Indonesia in recent times, along with the ratification of the RUU-PKS. Some people consider it a crime; others consider it unreasonable, so they think that the RUU-PKS is unnecessary in Indonesia. Then, is it true that marital rape is a crime? Why do so many still think of it as making it up if it is true? This topic is essential because marital rape is a form of violence that seems to be legalized in society. Whereas, National Commission on Violence Against Women reported that the cases of marital rape are always more than 100 cases every year. By using the literature research method that refers to the descriptive-qualitative research model and using Kate Millett's sexual-political theory. That marital rape is a crime that falls into sexual violence because it has an element of coercion in sexual intercourse. In addition, people who disagree with the criminalization of marital rape are caused by the existence of a patriarchal mindset in the culture of Indonesian society. Inherited customs and misconceptions of religion influence this mindset taught long ago. This research aims to explain why the RUU-PKS could be a tool to educate the public about marital rape so that it can gradually eliminate marital rape and patriarchy in Indonesia.